Assessment Of Textbook Published By Ministry of Religion Republic Indonesia: HOTS, MOTS, or LOTS? - Rahmawati, Rahmawati; Febriani, Suci Ramadhanti; Yasmadi, Yasmadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to analyze the assessment of Arabic language skills and linguistic elements in the book published by the Minister of Religion in 2020 for mapping assessments based on HOTS, MOTS, or LOTS. The research method used is descriptive qualitative based on content analysis techniques on assessment items listed in class X Madrasah Aliyah textbooks. Data was obtained through written sources, namely textbooks, as many as 392 assessment items, and other secondary sources, such as papers, articles, and books. The results of this study show that the percentage of assessments in the class X Arabic textbooks issued by the Decree of the Minister of Religion (KMA) of the Republic of Indonesia in 2020 leads to the following competencies: as much as 35% of the assessment items fall into the C2 category (understanding); 54% in category C3 (apply); and 9% fall into category C4 (analyze). The research findings identify that the form of assessment in the Arabic language textbook for class X KMA 2020 leads to the middle-order thinking skills level (MOTS), which is more dominant at the C3 (applying) level. The researchers recommend further research to develop Arabic teaching materials that lead to higher-order thinking skills (HOTS) through Bloom's Taxonomy framework.